Development of Obstacle Odyssey, an Interactive Game by Using GDevelop - Panjaitan, Cherlina Helena Purnamasari; Retno, Sujacka; Hasdyna, Novia (Gameology and Multimedia Expert, 2024)
Games are a medium that is in great demand by almost all ages, including children, teenagers and adults. As game technology develops which can be found on various platforms, games are not just mere entertainment but can also be given educational value in them. The Obstacle Odyssey game was built by applying educational values which are expected to improve the players' abilities in terms of tactical thinking. This Obstacle Odyssey game is an Arcade genre game. This game was built using Gdevelop using a no-code event system.